THE INTERPRETIVE SOCIOLOGY OF MICHEL MAFFESOLI:IMPLICATIONS FOR NURSING RESEARCH - Juliana Fernandes da Nóbrega; Rosane Gonçalves Nitschke; Ana Izabel Jatobá Souza; Evanguelia Kotzias Atherino dos Santos (Universidade Federal do Paraná, 2012)
This is a reflexive study on Maffesoli's Interpretive Sociology and its relation with works in the healthcare area. The text includes a brief biography of the author, the author's notions, the five theoretical assumptions and sensitivity. Maffesoli defends that "static rationalism", a symbol of modern thought, needs to give way to the post-modern "open rationality" - sensitive reason - which appeals to enthusiasm, to instinct. To Maffesoli, to analyze a phenomenon, it is necessary that there should be a balance between reason and feeling. Believing that there is "something more", beyond "numbers, measures and outcomes", scholars have proposed the use of sensitive reason in the research process. However, Interpretive Sociology, by favoring another vision of human relations, contributes heavily to research in academic circles, especially in Nursing research.